Research Advances in the Intervention of Inflammation and Cancer by Active Ingredients of Traditional Chinese Medicine - Huang, Yinghong; Cai, Tiange; Xia, Xi; Cai, Y; Wu, Xiao Yu (Journal of Pharmacy & Pharmaceutical Sciences, 2016)
A large body of evidence has shown that inflammation and cancer are strongly related. Thus anti-inflammatory agents have been investigated for cancer prevention and treatment in preclinical and clinical studies, including the nonsteroidal anti-inflammatory drugs (NSAIDs) and traditional Chinese medicine (TCM). In TCM, there exist a wide range of biologically active substances, such as saponins, flavonoids, alkaloids, polysaccharides, polyphenols, phenylpropanoids, and quinones. Many of these active ingredients have been reported to inhibit inflammation, activate inflammatory immune response, and/or inhibit cancer cell proliferation and tumor growth. Given the potential role of inflammation in cancer initiation and progression, the inflammatory tumor microenvironment, the cross-talks between inflammatory and cancer cells, and multitargeting activities of some TCM compounds, we summarize the current knowledge on the anti-inflammatory and anti-cancer properties of ingredients of TCM together with their underlying mechanisms in an integrated way. We hope to provide a reliable basis and useful information for the development of new treatment strategies of inflammation and cancer comprehensively using TCM and their active ingredients. This article is open to POST-PUBLICATION REVIEW. Registered readers (see “For Readers”) may comment by clicking on ABSTRACT on the issue’s contents page.